Bencana Alam Perspektif Al-Qur’an Analisis Kisah Nabi Nuh, Nabi Hud dan Nabi Luth (Kajian Tematik) - Alizaky Alizaky (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2020)
Disasters often afflict humans, in various forms, including hurricanes, earthquakes, floods and others. Incidents like this have happened in the past when the people were told in many verses of the Qur’an, in general this is usually closely related to the defiance of the previous ummah against the messengers of Allah SWT, immoral acts and worshiping other than Allah SWT, that means there is the relationship of every disaster that comes with human disobedience to Allah SWT. So from these problems, the writing of this thesis aims to find out "Natural Disaster Perspective of Al-Qur'an Analysis of the Story of Prophet Noah, Prophet Hud and Prophet Lut (Thematic Study)" This research is a research library or literature, which is based on two sources, namely primary sources (the holy book of al-Qur'an) and secondary sources (supporting books related to the subject). Because the method of interpretation used is a thematic or maudhui method, the steps are taken using the maudhui interpretation steps, namely tracking and compiling verses related to predetermined problems, the Makiyah and Madaniyah verses, compiling the verses coherently according to the chronology of the period of his descent, accompanied by knowledge of the background of the revelation of the verse or asbab an-nuzul, knowing the correlation (munasabah) of these verses in each of his letters, arranging the theme of the discussion in a fit, systematic, perfect and complete framework (outline ), complete the discussion and description with the hadith, if deemed necessary, so that the discussion becomes more perfect and clearer, studying these verses thoroughly and comprehensively. The results showed that the disasters that befell the people of Lut, Noah and Hud, have the same process of inviting da'wah to return to the way of Allah SWT and leaving immoral acts that have been carried out such as adultery, liking the same sex, drinking, being brutal, committing oppression, but the invitation is not accepted, the messengers of Allah SWT receive unjust treatment, so when the warning is not heard and is accompanied by repentance, then the punishment of Allah will come unexpectedly, in the form of earthquakes and fire stones the people of the Prophet Lut, the flash floods that befell the Prophet Noah and the hurricane that befell the people of Prophet Hud.